Determining prognosis of systemic candidiasis infection in rats with the polymerase chain reaction method - Jacinta Santhanam,; Siti Azura Zainon,; Chin, Chook Fung; Faezah Shekh Abdullah, (Universiti Kebangsaan Malaysia, 2010)
Candidiasis infections caused by the fungi Candida spp. are currently the most common systemic fungal infection in hospitalised patients. Diagnostic procedures involving culture or serological tests are either slow or lacking sensitivity and specificity. Thus polymerase chain reaction (PCR) assays which detect fungal DNA have been developed to provide a rapid, accurate diagnosis. In this study we evaluated a seminested PCR assay for the detection of systemic Candida albicans infection in laboratory animals. Adult Sprague-Dawley rats were infected with C. albicans by intravenous injection of yeast cells. Blood was collected from the animals every 3 to 4 days for extraction of DNA. Each week, 3 animals were sacrificed and their organs were cultured to confirm systemic C. albicans infection. The study period was 4 weeks (28 days). A seminested PCR was performed on DNA samples using universal fungal primers (ITS1 and ITS3) and a C. albicans specific primer (CALB1). The PCR product was detected by agarose gel electrophoresis. The PCR assay was able to detect C. albicans DNA in the blood samples of infected animals consistently from day 2 until day 25 post-infection. Organ culture of kidneys, liver and spleen revealed that the rats were systemically infected until day 21 post-infection and had recovered from infection (negative culture results) by day 28 post-infection. This study shows that the seminested PCR was an effective method to detect systemic C. albicans infection throughout the infection period. Therefore this assay is not only a diagnostic tool but has prognostic value as well for the monitoring of infection status.